Impacts of melt holding temperature on properties of the aluminum–copper–cullet metal composite (Journal of Pure and Applied Sciences (Science Forum), 2026)
The aluminum–copper–cullet (Al–Cu–CP) metal composite was fabricated at three different holding temperatures (800°C, 900°C, and 1,000°C, respectively) using the stir casting method. The composite was fabricated from Al, Cu, and CP. The holding temperature was varied in order to ascertain the optimum temperature for the fabrication of the composite. The Al–Cu–CP metal composite fabricated was characterized by checking its physical and mechanical properties in order to ascertain its potentials and application. The Al–Cu–CP metal composite fabricated at 800°C exhibited the best properties as the  properties of the composite fabricated at 900°C and 1,000°C were relatively inferior. Thus, 800°C is the optimum holding temperature for the fabrication of the Al–Cu–CP metal composite using the stir casting method.